Scale development theory and applications - DeVellis, Robert F.; Thorpe, Carolyn T. (Thousand Oaks, California SAGE Publications, Inc., 2022)
Scale Development: Theory and Applications, by Robert F. DeVellis and new co-author Carolyn T. Thorpe, demystifies measurement by emphasizing a logical rather than strictly mathematical understanding of concepts. The Fifth Edition includes a new chapter that lays out the key concepts that distinguish indices from scales, contrasts various types of indices, suggests approaches for developing them, reviews validity and reliability issues, and discusses in broad terms some analytic approaches. All chapters have been updated, and the book strikes a balance between including relevant topics and highlighting recent developments in measurement while retaining an accessible, user-friendly approach to the material covered."--
Chapter 1 Overview -- General Perspectives on Measurement -- Historical Origins of Measurement in Social Science -- Later Developments in Measurement -- The Role of Measurement in the Social Sciences -- Chapter 2 Understanding the Latent Variable -- Constructs Versus Measures -- Latent Variable as the Presumed Cause of Scale Item Values -- Path Diagrams -- Further Elaboration of the Measurement Model -- Parallel Tests -- Alternative Models -- Choosing a Causal Model -- Chapter 3 Scale Reliability -- Methods Based on the Analysis of Variance -- Continuous Versus Dichotomous Items -- Internal Consistency -- Coefficient Alpha -- Remedies to Alpha’s Limitations -- Coefficient Omega --Reliability Based on Correlations Between Scale Scores -- Reliability and Statistical Power -- Generalizability Theory -- Chapter 4 Scale Validity -- Content Validity -- Criterion-Related Validity -- Construct Validity -- What About Face Validity? -- Chapter 5 Guidelines in Scale Development -- Step 1: Determine Clearly What It Is You Want to Measure -- Step 2: Generate an Item Pool -- Step 3: Determine the Format for Measurement -- Step 4: Have Initial Item Pool Reviewed by Experts -- Step 5: Cognitive Interviewing -- Step 6: Consider Inclusion of Validation Items -- Step 7: Administer Items to a Development Sample -- Step 8: Evaluate the Items -- Step 9: Optimize Scale Length -- Chapter 6 Factor Analysis -- Overview of Factor Analysis -- Conceptual Description of Factor Analysis -- Bifactor and Hierarchical Factor Models -- Interpreting Factors -- Principal Components Versus Common Factors -- Confirmatory Factor Analysis -- Using Factor Analysis in Scale Development -- Sample Size -- Chapter 7 The Index -- How an Index Differs From a Scale -- Rules of Thumb for Differentiating an Index From a Scale -- Is It a Scale or an Index? Formal Methods for Distinguishing Effect and Causal Indicators -- Steps in Developing and Evaluating an Index -- Hybrid Measures -- Methods Based on Structural Equation Modeling -- Criticisms of Index Composites -- Chapter 8 An Overview of Item Response Theory -- Item Difficulty -- Item Discrimination -- Guessing, or False Positives -- Item-Characteristic Curves -- IRT Applied to Multiresponse Items -- Chapter 9 Measurement in the Broader Research Context -- Before Scale Development -- After Scale Administration.
Includes bibliographical references and index.
Keywords: Scaling (Social sciences).